Accurately Defining the Incidence and Associations of 90-Day Complications after Urethroplasty: Adverse Impact of Patient Comorbidities, Preoperative Bacteriuria and Prior Urethroplasty. Issue 2 (4th August 2022) - Noble, Ryan; Hoy, Nathan; Rourke, Keith
Abstract : Purpose: The purpose of this study was to determine the incidence of 90-day complications after urethroplasty and identify factors associated with them. Materials and Methods: A single-institution, 2-surgeon retrospective review was performed on patients undergoing urethroplasty from August 2003–June 2020. Variables included the incidence, type and Clavien-Dindo grade of complications, patient age, individual comorbidities, comorbidity component of the Charlson Comorbidity Index (CCI), smoking status, obesity (body mass index ≥35 kg/m 2 ), bacteriuria, type of urethroplasty, stricture etiology, length, location, prior endoscopic procedures, previous urethroplasty and preoperative suprapubic catheterization. The primary outcome was the incidence of significant 90-day complications defined as Clavien grade ≥2. Descriptive statistics were used to summarize the results and binary logistic regression was used to examine the factors associated with 90-day complications. Results: Of the 1, 611 patients included in the analysis, 90-day complications (Clavien ≥2) occurred in 7.9% (128/1, 611) and were wound related (3.5%), urinary tract infection (3.4%), cardiovascular (0.4%), catheter-related (0.2%), hematuria (0.1%) or retention (0.1%). On univariable binary logistic regression stricture location (p=0.04), stricture length (p=0.009), CCI (p <0.0001), prior urethroplasty (p=0.01) and bacteriuria (p=0.002) were associated with complications, while age (p=0.3), etiology (p=0.2), smoking (p=0.2), obesity (p=0.3), failed endoscopic treatment (p=0.8), indwelling suprapubic catheter (p=0.7) and type of urethroplasty (p=0.09) were not. On multivariable analysis, increasing CCI (Odds Ratio 1.31, 95% CI 1.10–1.56; p=0.003), prior urethroplasty (OR 1.86, 95% CI 1.09–3.17; p=0.02) and preoperative bacteriuria (OR 1.67, 95% CI 1.14–2.45; p=0.009) remained associated with 90-day complications. Conclusions: Patients with increased comorbidities, prior urethroplasty and preoperative bacteriuria are at higher risk for complications after urethroplasty and should be counseled accordingly in a shared decision-making model of care.